1998
DOI: 10.1017/s0025315400041606
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Biology of the Gregarious Mediterranean Vermetid GastropodDendropoma Petraeum

Abstract: The reproductive biology of the gregarious Mediterranean vermetid gastropod Dendropoma petraeum (Mollusca: Gastropoda) has been studied in the south-eastern coast of Spain. It apparently is a gonochorisric species with the sex ratio biased toward females (71%). A broad peak of more intense reproductive activity occurs in spring months and an inactive reproductive period during winter. The gonad of the males develops about two months before those of females, and storage of sperm by females has been observed. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
57
2
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 19 publications
7
57
2
3
Order By: Relevance
“…In males of Serpulorbis imbricatus, Nishiwaki (1969) found testes well developed during October-March but in a degenerated state when females were depositing and brooding capsules in May-August. Calvo et al (1998) found that males of Dendropoma petraeum developed gonad 2 months before females. In Hadfield's vermetid, however, we did not see any spermatophores or sperm in squash preparations of tissue taken from brooding adults nor were ripe males and spermatophores seen in large specimens examined in August (2 to 3 months before brooding season) or November (presumably early in the brooding season) (M. G. Hadfield, pers.…”
Section: Invasive Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…In males of Serpulorbis imbricatus, Nishiwaki (1969) found testes well developed during October-March but in a degenerated state when females were depositing and brooding capsules in May-August. Calvo et al (1998) found that males of Dendropoma petraeum developed gonad 2 months before females. In Hadfield's vermetid, however, we did not see any spermatophores or sperm in squash preparations of tissue taken from brooding adults nor were ripe males and spermatophores seen in large specimens examined in August (2 to 3 months before brooding season) or November (presumably early in the brooding season) (M. G. Hadfield, pers.…”
Section: Invasive Potentialmentioning
confidence: 99%
“…(6) Males may be present but very rare. Calvo et al (1998) reported a population of Dendropoma petraeum that was gonochoric but had a preponderance of females (71%). The apparent absence of males, at least while females are brooding, suggests the possibilities of long-term sperm storage, self-fertilization with low male allocation, or parthenogenesis.…”
Section: Invasive Potentialmentioning
confidence: 99%
“…The brooding of stalked egg capsules seems to be the rule in Thylacodes (MORTON 1951, HADFIELD et al 1972, HUGHES 1978a,b, SCHEUWIMMER & NISHIWAKI 1982, KELLY 2007, Petaloconchus (HADFIELD 1970, 1989, HADFIELD et al 1972, HUGHES 1978b, BANDEL 1984, STRONG 2003, KELLY 2007, Vermetus (MORTON, 1965, MILOSLAVICH & PECHAZADEH 1992, BIELER 1995, CALVO & TEMPLADO 2004 and Thylaeodus (BIELER 1995, STRATHMANN & STRATHMANN 2006; whereas in Dendropoma spp., they are more often free inside the mantle cavity (MORTON 1965, HADFIELD et al 1972, HUGHES 1978a, CALVO et al 1998, PACHECO & LAUDIEN 2008. However, there are some exceptions, as presented here, and also observed by HADFIELD et al (1972), LEWIS (1974), andSCHIAPARELLI &METIVIER (2000).…”
Section: Discussionmentioning
confidence: 99%
“…These conditions are not always obtained. The increase in the number of animal and vegetable species that have become extinct in many Mediterranean areas has motivated the list of endagered species included in Amnex II and in Appendix II ( Bouderesque et al, 1996 andCalvo et al, 1998). Even some areas along the northwest coast of Sicily, Capo Gallo and Isola delle Femmine, have been proposed as nature reserves .…”
Section: Introductionmentioning
confidence: 99%
“…The latter, in particular, described the anatomy of the female and male reproductive organs of Vermetus triqueter and V. semisurrectus, giving a brief summary of their histological features. A great bulk of research has been done on the reproduction of various vermetid genera, in particular on the formation of the egg capsules, on their relationship with the mantle cavity, on the number of embryos at different maturation stages found inside the capsule, on their development and hatching (Morton, 1965;Hadfield, 1969Hadfield, , 1970Hadfield et al, 1972;Hughes and Lewis, 1974;Hughes, 1979b;Miloslavich and Penchaszdeh, 1992;Calvo et al, 1998). The fertilization mechanism of some vermetids is known and the description of the male genital tract has been given; however, no bibliography or images of the male gonad of the vermetid D. petraeum have been found.…”
Section: Introductionmentioning
confidence: 99%